Integrasi Barcode Pada Administrasi Sirkulasi Perpustakaan SMP Negeri 1 Tenggarong Seberang - Ummul Hairah (STMIK KHARISMA Makassar, 2016)
The school library as an educational component that support teaching and learning process needs to pay attention to service standards. Not only in providing library services, administration services for library circulation also required to be done quickly, accurately and effectively. To overcome obstacles due process is still manual it is necessary to apply computerized technology through the development of desktop applications with the integration of barcode using the programming language Visual Basic 6.0. This application can manage data archiving collections of books, libraries data members and inventory. Administration circulating library that includes: the process of borrowing and returning books, book collection data searching, llibrary members registration and printing of a membership card. In archiving and borrowing and repayment process is integrated with barcode technology to more easily and accurately. In addition, the system also processes reports about the number of books owned by the library, reports the number of members of the library, borrowing books and reports. To complete this application, added features, including presence of visits, setting keijakan related to the process of circulation, and to avoid things that are not desirable, there is also a database backup facility.